A Frequency of fimA Genotypes of P. gingivalis in Rheumatoid Arthritis Patients and Control group.: Genotypes of P. gingivalis in Rheumatoid Arthritis - Jasim, Haneen; Al-Turaihi, Thanaa; Hadi, Zainab; abbas, Jawad (Medical Science Journal for Advance Research, 2023)
Rheumatoid arthritis (RA): Chronic inflammatory polyarthritis, an autoimmune response targeting citrullinated antigens, due to destructive synovial joint inflammation. Porphyromonas gingivalis, a gram-negative bacterium residing in the subgingival tissues of the oral cavity, has been implicated in the association with RA, mainly due to the identification of a bacterial enzyme known as peptidyl arginine deaminase (PAD). The presence of this enzyme in P. gingivalis suggests its potential role in RA development by generating citrullinated antigens. Aims: The association between P. gingivalis and the development of anticitrullinated peptide antibody (ACPA) and if its role as an environmental risk factor of RA. Methods: This case-control study involved a total 140 participants, collection of blood and gingival crevicular fluid (GCF) samples from the participants, various tests were conducted, Specific PCR primers targeting fimA genotypes of P. gingivalis were utilized to amplify the relevant genetic regions.Statistical analysis used: Statistical Package for the Social Sciences (SPSS) version 26, a T-test and Chi-square (χ^2) test were utilized. Results: The p-values for ESR, ACCP, and IL-17 were 0.0001, 0.02, and 0.0001, respectively, indicating strong statistical significance for RA patients. Among the RA patients with P. gingivalis infection and the RA patients without P. gingivalis infection the analysis did not reveal a statistically significant difference in mean of ACCP and all biomarkers between the two groups (p-value=1.000) Conclusions: No association between P. gingivalis and the development of ACPA, the rise in ESR levels as disease severity escalates underscores the potential practicality of using ESR as an indicator to evaluate disease activity in RA, a trend towards a higher occurrence of gum problems among RA patients especially in category of patients developed gum problems before the onset of RA.